2007
DOI: 10.1007/s12028-007-9034-y
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Rhythm in Aneurysmal Subarachnoid Hemorrhage

Abstract: Abnormal cosinor parameters provided additional predictive information in relation to outcome, beyond the impact of initial neurologic condition. Further research is needed to understand the pathophysiology of temperature regulation following cerebral aneurysm rupture and to determine if temperature management strategies can alter outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In 15 patients, Tweedie et al [19] showed that the CBT amplitude was > 0.15°C in non-survivors. In 86 patients with traumatic brain injury, Kirkness et al reported significantly higher temperature amplitude of 0.1°C among non-survivors [40]. Conversely, other studies found that a decreased amplitude during the ICU stay was associated with the severity of illness and the mortality rate [41,42].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In 15 patients, Tweedie et al [19] showed that the CBT amplitude was > 0.15°C in non-survivors. In 86 patients with traumatic brain injury, Kirkness et al reported significantly higher temperature amplitude of 0.1°C among non-survivors [40]. Conversely, other studies found that a decreased amplitude during the ICU stay was associated with the severity of illness and the mortality rate [41,42].…”
Section: Discussionmentioning
confidence: 98%
“…Our protocol included a large number of patients, as compared to previous studies [21,28,37,42,43]. Temperature measurements were collected from a central site-this point being the most common limitation encountered in other studies [21,28,37,40,44]. Bladder temperature monitoring is a validated method for determining CBT-with a minimal error margin and a good correlation with CBT [45].…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysmal subarachnoid hemorrhage (SAH) is believed to be a largely unpredictable, spontaneous event. However, the formation and rupture of cerebral aneurysms has been shown to be associated with multiple factors, including the characteristics of the aneurysm, the age of the patient, blood pressure, and changes in body temperature [1] , [2] . Regional weather patterns and seasonal changes have also been hypothesized to impact the risk of rupture of cerebral aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…In certain populations, such as those with neurological insults, fever is associated with poor outcomes (Wartenberg et al. 2006, Kirkness et al. 2008) and should be avoided (Adams et al.…”
Section: Introductionmentioning
confidence: 99%